The Leviathan Field Triggering a Maritime Border Dispute Cyprus, Israel, and Lebanon†. Issue 3 (3rd July 2017) - Aboultaif, Eduardo Wassim
ABSTRACT: The discovery of the Leviathan field on the eastern shores of the Mediterranean has triggered a maritime dispute between Lebanon, Israel, and Cyprus. The aim of this paper is to construct the maritime borders based on the Law of the Seas Convention and previous rules by the International Court of Justice. Equidistant lines and the concept of equity will be applied to the method of drawing the maritime borders. In addition, theories of conflict resolution will be utilized in order to manage the natural resources between the three states.